The Rumen Microbiome Composition of Raramuri Criollo and European Cattle in an Extensive System - Adrian Maynez-Perez; Francisco J. Jahuey-Martínez; José A. Martínez-Quintana; Michael E. Hume; Robin C. Anderson; Agustín Corral-Luna; Felipe A. Rodríguez-Almeida; Yamicela Castillo-Castillo; Monserrath Felix-Portillo (Microorganisms)
Understanding the relationship between Raramuri Criollo cattle (RC) and their microbial ruminal ecosystem will help identify advantageous characteristics of adapted cattle as alternatives to achieve sustainable beef production systems. Our objective was to characterize the rumen microbiome of RC in comparison to Angus and Hereford breeds (European, E) and the cross between them (E × RC). Ruminal fluid was collected from 63 cows in their second productive cycle after grazing in the same paddock for 45 d, in the dry (n = 28) and rain (n = 35) seasons. DNA from ruminal fluid was isolated for 16s rRNA gene next-generation sequencing. The data were analyzed with QIIME2 and compared against the SILVA 16s rRNA database. Beta diversity was different (p < 0.05) between RC and E in both seasons. A microbial core was represented by the most abundant phyla. Planctomycetes and Spirochaetes represented above 1% in the rain season and below 1% in the dry one, whereas Euryarchaeota was below 1% and around 3%, respectively. LEfSe analysis identified differentiated (p < 0.05) key microbial groups that explain the differences between lineages at different taxonomic levels, reflecting the ability of the rumen ecosystem of RC cattle to adapt to hostile environmental conditions by having microbial groups specialized in the degradation of highly fibrous content.